dBASE III plus : programmers Rererence guide. - Ashton-Tate. (Singapore Tech Publications., 1987)
A data base management system for use in a variety of applications. Instructs users in how to create, store, edit, retrieve, and control data. New features include an improved user interface, new programming commands and functions, interactive debugging, and an on-line help system, among others. Supports network operating mode.
System (2 disks) -- Sample programs & utilities -- On-disk tutorial -- Administrator (2 disks) -- Application generator.
Includes index.
Not copy-protected.
Issued also in versions for other systems.
System requirements: IBM PC, AT, XT, or PS/2, or 100% compatible computers; minimum 256K RAM (384K recommended); PC-DOS 2.00 or higher (384K required for PC-DOS 3.00 or higher); 1 (minimum 360K) disk drive and a fixed-disk drive or 2 (minimum 360K) disk drives; monochrome or color monitor; 80-column printer (optional).
Keywords: Database management -- Software